Comer y ser : la alimentación como política de la diferenciación en la América española, siglos XVI y XVII (2016)
ABSTRACT: This paper demonstrates that food served as a marker of social differentiation during the 16th and 17th centuries in the Spanish possessions in America, not only in economic terms but also in the sense that food was associated with the social stratum to which a person belonged. Each one was oblidged to eat foods associated with his or her "natural" stratum. This complex hierarchical model of society was based on European patterns coming from the Middle Ages, such as the Great Chain of Being and humoral theory. This model was reinforced in the early modern period, and it took on new characteristics in America, where it was used to differentiate Spaniards, Creoles, Mestizos and Indians.